Analisis Semiotika Ferdinand de Saussure Desain Kemasan Bakpia Kukus Tugu Jogja - Atiqoh, Nazihah Almas; Turrohmah, Nadhifa; Habibi, Muhamad Lutfi (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2022)
This paper interprets the use of signs on the Bakpia Kukus Tugu Jogja packaging which is attractive, looks different,and has a strong influence on the audience's decision to buy the products. The purpose of this study was to determine the meaning of verbal and visual signs based on the theory of visual communication design contained on the front of the packaging design. The analysis units in this study are the visual communication design elements and principles which are grouped based on proximity in Gestalt theory. This study method uses Ferdinand de Saussure's semiotic analysis which states that the relationship between signifier and the signified produces sign. The findings show that Bakpia Kukus Tugu Jogja uses the relationship between verbal and visual signs by displaying the meaning that the product has an identity in the form of modern and luxurious product innovations but does not forget the noble values of wise and equal Javanese culture.